Cultural Representations of Klaipeda: Sleepy Town, Domestic People, Kitchen-Sink Multiculturalism... - Gedutis, Aldis (Sociologija. Mintis ir veiksmas, 2011)
The aim of this article is to reconstruct ways in which Klaipeda’s culture and its representations changed during the first two decades of independence. The article is based on media analysis and a series of interviews with representatives of different cultural fields. The interviewees are grouped into four categories: (1) official cultural policy-makers; (2) artists and cultural workers (curators, producers, managers etc.); (3) representatives of different subcultures; (4) culturally informed intellectuals. The qualitative interview analysis concentrates on the following aspects and dynamics: (1) the most influential ‘ambassadors’ of Klaipeda’s culture; (2) culturally significant places and spaces; (3) representative events and cultural institutions; (4) cultural symbols of Klaipeda; (5) representative routes; (6) the (possible) multiculturalism of Klaipeda. The main questions to be addressed by the article are as follows: do current approaches enable us to discover anything that is invisible from the perspective of dominant cultural narratives? Who are the best representatives and representations of Klaipeda’s culture? Who controls the cultural identity of Klaipeda? In what ways are cultural identities and ideologies constructed? Are there any alternatives to dominant cultural representations available?
Keywords: Klaipėda; urban culture; urban identities; cultural narratives